Transcriptome and metabolome analyses of anthocyanin biosynthesis in post-harvest fruits of a full red-type kiwifruit (Actinidia arguta) ‘Jinhongguan’ - Ye, Lixia; Bai, Fuxi; Zhang, Lei; Luo, Minmin; Gao, Lei; Wang, Zhi; Peng, Jue; Chen, Qinghong; Luo, Xuan (Frontiers in Plant Science, 2023)
Anthocyanin is the main component of pigment in red-fleshed kiwifruit. 'Jinhongguan' is a new cultivar of Actinidia arguta with red peel and flesh after harvest. However, the specific types of anthocyanin in the 'Jinhongguan' fruit and its biosynthesis pathways remain largely unknown. Here, the total anthocyanin content in the fruit color conversion process was determined. The results showed that total anthocyanin content increased with the deepening color of the peel and flesh. To identify the genes related to anthocyanin biosynthesis and the types of anthocyanins in the 'Jinhongguan' fruit, a combined analysis of transcriptome and anthocyanin-targeted metabolome was carried out. A total of 5751 common differentially expressed genes (DEGs) at different stages of peel and flesh were identified, of which 2767 were common up-DEGs and 2976 were common down-DEGs. KEGG and GO enrichment analyses showed that the common up-DEGs were significantly enriched in anthocyanin synthesis-related pathways, suggesting some up-DEGs are involved in anthocyanin biosynthesis. In total, 29 metabolites were detected in the flesh by anthocyanin-targeted metabolome. Among these, nine were differential accumulation metabolites (DAMs) in comparison to red flesh vs green flesh. Six DAMs were up-regulated, with five of them were cyanidins. The content of cyanidin-3-O-galactoside was much higher than that of other DAMs, making it the main pigment in 'Jinhongguan'. Moreover, a total of 36 anthocyanin synthesis-related structural genes, 27 MYB transcription factors (TFs), 37 bHLH TFs and 9 WDR TFs were screened from the common DEGs. Correlation analysis of transcriptome and metabolome revealed that 9 structural genes, 6 MYB TFs, 6 bHLH TFs and 1 WDR TF were significantly associated with cyanidin-3-O-galactoside. Further, qRT-PCR analysis demonstrated that structural genes (AaPAL3, Aa4CL3, AaCHS2/3/8/9/11, AaDFR1/2, AaANR1, UFGT3a and UFGT6b) and TFs (MYB108, bHLH30, bHLH94-1 and WD43) play important roles in cyanidin biosynthesis. Overall, this study identified cyanidin-3-O-galactoside as the main anthocyanin type and revealed key candidate genes of red coloration of post-harvest fruit in Actinidia arguta. These findings provided new insights into the color formation mechanism of post-harvest fruit and offered a theoretical basis for color regulation in kiwifruit.